Influence of the age of Oxydia vesulia eggs on parasitism by Trichogramma maxacalii - Oliveira, Harley Nonato de; Pratissoli, Dirceu; Zanuncio, José Cola; Serrão, José Eduardo (Pesquisa Agropecuaria Brasileira, 2003)
Trichogramma is among the most important genus of biological control. This research evaluated the parasitism potential of Trichogramma maxacalii on eggs of Oxydia vesulia at different embryonic developmental stages. Twenty five eggs of O. vesulia one, three, five and seven days old were offered to the parasitoid in a fifteen replication essay, for a period of 24 hours. Parasitism rate, viability, sexual rate and females that parasited were not influenced by the age of O. vesulia eggs. Low parasitism rate of T. maxacalii in eggs of O. vesulia was found but more than 70% of the females of this parasitoid showed parasitism on eggs up to five days old.